Chronic allergic skin diseases in men: the influence of age-related dishormonal status - N. Yu. Reznichenko (Zaporožskij Medicinskij Žurnal)
The study of the etiology and pathogenesis of allergic skin diseases, as well as a reasonable selection of their optimal treatment are extremely relevant problems of modern medicine. Changes in the sex and gonadotropic hormones levels, which occur in patients with chronic allergic dermatoses and affect them, are studied insufficiently.